Are clinical practice guidelines for low back pain interventions of high quality and updated? A systematic review using the AGREE II instrument - G. Castellini; V. Iannicelli; M. Briguglio; D. Corbetta; L. M. Sconfienza; G. Banfi; S. Gianola (BMC, 2020)
Abstract Background Clinical practice guidelines (CPGs) provide recommendations for practice, but the proliferation of CPGs issued by multiple organisations in recent years has raised concern about their quality. The aim of this study was to systematically appraise CPGs quality for low back pain (LBP) interventions and to explore inter-rater reliability (IRR) between quality appraisers. The time between systematic review search and publication of CPGs was recorded. Methods Electronic databases (PubMed, Embase, PEDro, TRIP), guideline organisation databases, websites, and grey literature were searched from January 2016 to January 2020 to identify GPCs on rehabilitative, pharmacological or surgical intervention for LBP management. Four independent reviewers used the Appraisal of Guidelines for Research and Evaluation II (AGREE II) tool to evaluate CPGs quality and record the year the CPGs were published and the year the search strategies were conducted. Results A total of 21 CPGs met the inclusion criteria and were appraised. Seven (33%) were broad in scope and involved surgery, rehabilitation or pharmacological intervention. The score for each AGREE II item was: Editorial Independence (median 67%, interquartile range [IQR] 31-84%), Scope and Purpose (median 64%, IQR 22-83%), Rigour of Development (median 50%, IQR 21-72%), Clarity and Presentation (median 50%, IQR 28-79%), Stakeholder Involvement (median 36%, IQR 10-74%), and Applicability (median 11%, IQR 0-46%). The IRR between the assessors was nearly perfect (interclass correlation 0.90; 95% confidence interval 0.88-0.91). The median time span was 2 years (range, 1-4), however, 38% of the CPGs did not report the coverage dates for systematic searches. Conclusions We found methodological limitations that affect CPGs quality. In our opinion, a universal database is needed in which guidelines can be registered and recommendations dynamically developed through a living systematic reviews approach to ensure that guidelines are based on updated evidence. Level of evidence 1 Trial registration REGISTRATION PROSPERO DETAILS: CRD42019127619 .